Software and algorithmic complex for evaluating the efficiency of an automated optical-electronic system - Lovtsov, Dmitry; Gavrilov, Dmitry (2021 International Seminar on Electron Devices Design and Production (SED), 2021)
This paper presents a set of operation quality assessments of systems intended for detecting and localising objects of interest depending on the content of input video. The development of an input video registration generator has been carried out based on object and camera movement trajectories and on image distortions in a frame. A description of the main modules of the complex has been presented and experimental studies of localisation detection algorithms have been conducted.